Diagnostic Tools Applied by ICARDA’s Germplasm Health Unit (GHU) for Detection of Pests and Diseases Transmitted via Legume and Cereal Seeds - Kumari, Safaa; Moukahel, Abdulrahman; El Miziani, Inaam; Darwish, Iman (Arab Society for Plant Protection, 2023)
Seeds of cereals (wheat, barley) and legumes (faba bean, lentil, chickpea, grasspea) are important exchange materials for farming, crop production, and research at national, regional, and international levels, but with the exchanges comes the danger of introducing new pests (fungi, bacteria, viruses, nematodes, and insects). ICARDA’s Germplasm Health Unit (GHU) is responsible for the monitoring, clearance, and documentation of safe germplasm movement at the Center. All incoming and outgoing genetic resources and breeding germplasm must pass through a strict quarantine monitoring system, including seed health testing. To confirm the health status of seed samples, the GHU conducts different types of tests based on the crops and the nature of the target pest. These tests can be classified into the following four distinct detection groups: direct inspection, incubation tests, immunoassays, and molecular tests. Ideally, seed health tests should be sensitive, specific, rapid, robust, low-cost, and simple to implement and interpret. Thus, ICARDA’s GHU applies different detection assays as part of the monitoring and management system, i.e. (i) visual inspection and floating test for stored insects, (ii) centrifuge washing, agar plate and freezing blotter tests for fungi, (iii) TBIA and ELISA for viruses, (iv) nematode extraction test for nematodes, and (v) agglutination test for bacteria. These tests permit rapid analysis of a large number of samples at a relatively low cost. ICARDA's GHU also developed and applied molecular tools such as high throughput, short lead times, and accurate assays. To fulfill legal and regulatory requirements for certified seed classes and allow for seed movement across international boundaries, ICARDA’s GHU processes annually over 50k samples tested for around 650k diagnostic reactions, for the purpose of short- and long-term conservation, distribution to a minimum of 90 countries and elimination of approximately 10-15% of pest-contaminated samples that could not be curated using phytosanitary treatments. The rejected samples were contaminated generally with fungi, nematodes, and viruses.